Maintaining Social Harmony Through Historical Learning Based on Local Wisdom of Indigenous Peoples in Maluku - Oruh, Shermina; Agustang, Andi; Ufie, Agustinus (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2022)
This research unveiled the local wisdom values of wawar tradition that have been passed down from generation to generation among indigenous people in Kei islands that can be the driving force and conclusion to various social phenomena such as conflict, violence, and radicalism. This is a qualitative study with a descriptive analytical approach to 35 informants as the respondents. The results show that Wawarâ€™s local wisdom values, such as Tet Yaa, can manifest respect for and respect for attitudes, actions, words, and actions concretely in everyday life. Ain Ni Ain can manifest belonging to each other, brotherhood, loving others despite different religions, ethnicities and social statuses. Ha Maren, Yel Lim can embody the attitude of helping, giving and receiving in all aspects of life. On the other hand, the findings indicated that wawar tradition was a local wisdom capable of fostering an atmosphere of civilization and social order since this tradition contained social and moral values, which were able to gather and organize the social integrity of the community from all walks of life inhabiting Kei islands. Mutual respect and sharing, spirit of brotherhood and harmony were maintained amidst the ever growing onslaught of modern culture. Hence, wawar local culture as the identity of indigenous peoples among the school and students can be developed into learning sources so that education is able to prepare future generations who have cultural identity and self-integrity based on the values of local cultures and traditions.Â